Evaluation of Some Selective Surfaces Used for Solar Thermal Conversion Using the Calorimetric Method - Lahwal, Ali S (University of Zawia Journal of Natural Sciences, 2026)
Knowledge of the selective radiative properties of surfaces is essential for the proper design of solar thermal collectors. Experimental results must directly reflect the conditions under which a surface will operate in order to accurately evaluate selective coatings for potential use in solar collectors. To achieve this, an instrument based on calorimetric techniques has been developed. It measures the solar absorptivity (α) and infrared (IR) emissivity (ε) of surfaces. These measurements determine the spectral selectivity of surfaces and assess their suitability for solar energy applications. The absorptivity (α) and total hemispherical emissivity (ε) are calculated as functions of temperature is measured by observing the rate at which a thermally isolated sample in an evacuated chamber heats up under real or simulated solar radiation. Emissivity is determined by measuring the rate at which the sample cools when shaded. These parameters allow comparison of the relative efficiencies of different surfaces over a range of operating temperatures. A graphite sheet was used as a blackbody reference to calibrate the instrument, and it was found that its absorptivity and emissivity are nearly equal, with values of approximately 0.94. Two additional samples were tested: a copper selective surface coated with aluminum and painted black, and an aluminum surface with V-grooving coated with a selective black paint. The results indicate that the copper-based surface is more suitable for solar collector applications than the aluminum surface, owing to the significant difference between its absorptivity and emissivity (α=0.95,ε= 0.25), which leads to higher thermal efficiency